2021
DOI: 10.21203/rs.3.rs-281239/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

D-dimer-to-platelet Ratio as a Novel Marker of in-hospital Adverse Outcomes Among Patients With Acute Pulmonary Embolism: a Single-center Retrospective Study

Abstract: Background: This retrospective study aimed to evaluate the value of D-dimer to platelets ratio (DPR) in predicting the in-hospital prognosis of patients with acute pulmonary embolism (APE).Methods: We retrospectively reviewed the medical records of 237 patients with APE admitted from January 2016 to August 2020. The associations between the DPR and other predictors and serious adverse events were analyzed with univariate and multivariate analyses.Results: A total of 134 (56.5%) patients were categorized into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In the literature, DPR was used as a new marker of risk classification in patients diagnosed with PTE, and it was observed that the PTE clinic was worse in patients with increased DPR compared to other patients [ 7 ]. In another study, increased DPR was found to be significant in differentiating preeclampsia from normal pregnancy and gestational hypertension [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, DPR was used as a new marker of risk classification in patients diagnosed with PTE, and it was observed that the PTE clinic was worse in patients with increased DPR compared to other patients [ 7 ]. In another study, increased DPR was found to be significant in differentiating preeclampsia from normal pregnancy and gestational hypertension [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer in plasma is a fibrin breakdown product. Coagulation, fibrinolysis, and thrombotic clots all raise D-dimer levels in the blood [ 7 ]. The D-dimer test, on the other hand, is not specific.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation